2018
DOI: 10.1021/acs.jpcc.8b00250
|View full text |Cite
|
Sign up to set email alerts
|

A Car–Parrinello Molecular Dynamics Simulation Study of the Retro Diels–Alder Reaction for Partially Saturated 2-Pyrones in Water

Abstract: 2-Pyrones have been identified as potential platform molecules derived from biomass to produce high-value chemicals. Theoretical studies utilizing density functional theory (DFT) simulations have shown the partially saturated form of these molecules undergoing a retro Diels−Alder (rDA) reaction in both vapor and solvent conditions. Developing an understanding of the effect of solvent media is crucial to improve the processing of these biomass-derived compounds. In this context, DFT simulations had shown limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Polar solvents were observed to preferentially to reduce the activation barrier as compared to the nonpolar solvents due to the relative stabilization of the polarized transition state . Further, in order to account for the effect of solvent dynamics on the reaction kinetics of rDA reaction of partially substituted 2-pyrones, Car–Parrinello Molecular Dynamics (CPMD) simulations were employed . A relative lowering in the activation barrier was observed due to the dynamic behavior of the solvent, which was differentially interacting with the reactant and the activated complex .…”
Section: Ring-opening and Decarboxylation Of Cyclic Estersmentioning
confidence: 99%
See 2 more Smart Citations
“…Polar solvents were observed to preferentially to reduce the activation barrier as compared to the nonpolar solvents due to the relative stabilization of the polarized transition state . Further, in order to account for the effect of solvent dynamics on the reaction kinetics of rDA reaction of partially substituted 2-pyrones, Car–Parrinello Molecular Dynamics (CPMD) simulations were employed . A relative lowering in the activation barrier was observed due to the dynamic behavior of the solvent, which was differentially interacting with the reactant and the activated complex .…”
Section: Ring-opening and Decarboxylation Of Cyclic Estersmentioning
confidence: 99%
“…Further, in order to account for the effect of solvent dynamics on the reaction kinetics of rDA reaction of partially substituted 2-pyrones, Car–Parrinello Molecular Dynamics (CPMD) simulations were employed . A relative lowering in the activation barrier was observed due to the dynamic behavior of the solvent, which was differentially interacting with the reactant and the activated complex . These mechanistic insights are suggested to provide a unique opportunity to engineer the biocatalytic part so as to synthesize the 2-pyrone molecule as a precursor with different substituents, and to target the synthesis of the valuable chemical as shown in Figure . , …”
Section: Ring-opening and Decarboxylation Of Cyclic Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…For the unusual regio-and stereo-selectivity of DA reactions, selected works related to the inverse DA reaction are mentioned in the following. Shrivastav et al studied the reaction energetics and kinetics of 2-pyrone complex undergoing the retro DA reaction [23]. They also calculated the free energy surface (FES) of the DA reaction using Car-Parrinello molecular dynamics with MetaD to obtain the Gibbs activation energy.…”
Section: Introductionmentioning
confidence: 99%
“…A lowering of the free energy barrier has been reported for a solvated retro-Diels-Alder reaction using 50 water molecules (in-water) in comparison to the vapor phase reaction. The authors used Car-Parrinello molecular dynamics 15 and concluded that water solvent is pivotal to this 1a; R=O, Hydrogen-bond-"on" 1b; R=S, Hydrogen-bond-"off"…”
mentioning
confidence: 99%